Development of Digital Interactive Modules for Teaching Chemical Bonding of Grade XI Senior High School Students - Sari, Irfani Winda; Enawaty, Eny; Erlina (Universitas Pendidikan Mandalika, 2025)
This study aims to determine the feasibility of an interactive electronic module on chemical bonding for 11th-grade high school students, as well as to describe student responses to its use. The study is a type of Research and Development (R&D) using the 4D development model (Define, Design, Develop, and Disseminate), though it is limited to the Develop stage. Data collection instruments included feasibility assessment sheets and student response questionnaires. The module’s feasibility was assessed by three experts based on language, content, and media aspects. The results showed an average feasibility percentage of 95.51%, categorized as highly feasible. The response test was conducted on a limited basis with 30 students from grade XI at SMA N 1 Sungai Raya, yielding an average response percentage of 87.25%, categorized as very good. Based on these results, the interactive electronic module was deemed feasible and received positive responses from students, making it a potential alternative for engaging and interactive learning in chemical bonding.